Stylosanthes rostrata(Leguminosae), a New Combination from Argentina and Uruguay - Vanni, Ricardo Oscar (2009)
As part of the revision of the genus Stylosanthes Swartz (Leguminosae) from South America, material from Corrientes, Argentina, described by Burkart as S. gracilis Kunth var. rostrata Burkart, is recognized at species rank as S. rostrala (Burkart) Vanni.